2009
DOI: 10.1007/s11156-008-0104-9
|View full text |Cite
|
Sign up to set email alerts
|

Interest rate risk of German financial institutions: the impact of level, slope, and curvature of the term structure

Abstract: German financial institutions, Interest rate sensitivity, Term structure, Nelson–Siegel approach, G12, G21, G22,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 58 publications
4
35
1
2
Order By: Relevance
“…First, a significantly negative effect of movements in interest rates on banking firms' stock returns is generally documented, and it has been commonly attributed to the maturity mismatch between banks' assets and liabilities (Flannery and James, 1984;Elyasiani and Mansur, 1998;Au Yong and Faff, 2008;Czaja et al, 2009 and.…”
Section: Review Of Literaturementioning
confidence: 99%
“…First, a significantly negative effect of movements in interest rates on banking firms' stock returns is generally documented, and it has been commonly attributed to the maturity mismatch between banks' assets and liabilities (Flannery and James, 1984;Elyasiani and Mansur, 1998;Au Yong and Faff, 2008;Czaja et al, 2009 and.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Second, numerous authors have observed that the factors (level, slope and curvature) extracted from the NS model are insensitive to the choice of τ (see, among others, Nelson and Siegel 1987;Barrett et al 1995;Willner 1996;Dolan 1999;Czaja et al 2009;Favero et al 2012). More recently, Annaert et al (2013) estimated the parameters of the NS model for τ fixed at 1.37 (as in Diebold and Li 2006), and for τ fixed at 3 (as in Fabozzi et al 2005) for Euro spot rate curves, obtaining very similar results and being unable to conclude which of the two τ values is more suitable.…”
Section: Methodology and Datamentioning
confidence: 99%
“…This analysis shows that banks' market valuations were not affected by the holding of government debt by Italy, Spain, Portugal and Ireland. Finally, statistical analyses (Flannery & James, 1984;Czaja et al, 2009) find that bank stock returns are more sensitive to interest rate changes than the stock returns of other companies.…”
Section: Literature Reviewmentioning
confidence: 99%